2016
DOI: 10.1248/cpb.c16-00527
|View full text |Cite
|
Sign up to set email alerts
|

2-Azolylchromone Derivatives as Potent and Selective Inhibitors of Monoamine Oxidases A and B

Abstract: A series of 2-azolylchromone derivatives were synthesized and their monoamine oxidase (MAO) A and B inhibitory activities were evaluated. Of the synthesized compounds, compounds 1b, 2b, 4a-c, 5b and 7b showed potent inhibitory activities against MAO-A (IC 50 values, 1b: 0.32 µM; 2b: 0.14 µM; 4a: 0.11 µM; 4b: 0.023 µM; 4c: 0.15 µM; 5b: 0.59 µM; 7b: 0.19 µM) and 4a, c, 5a, c, 6c and 8c for MAO-B (IC 50 values, 4a: 0.028 µM; 4c: 0.019 µM; 5a: 0.73 µM; 5c: 0.28 µM; 6c: 0.28 µM; 8c: 0.27 µM). These data suggest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 20 publications
0
21
0
1
Order By: Relevance
“…Cytotoxicity of a compound is more valuable when it is selective. Although the chemical structures of all 24 compounds used in this study have already been reported (Table I) (4,15), the present study is the first that investigated the relative potency of TS of all…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cytotoxicity of a compound is more valuable when it is selective. Although the chemical structures of all 24 compounds used in this study have already been reported (Table I) (4,15), the present study is the first that investigated the relative potency of TS of all…”
Section: Discussionmentioning
confidence: 99%
“…were synthesized by the conjugated addition reactions of 3-iodochromone derivatives with selected azoles, according to previous methods (4). All compounds were dissolved in DMSO at 40 mM and stored at -20˚C before use.…”
Section: Synthesis Of Test Compounds 2-(1h-mentioning
confidence: 99%
See 1 more Smart Citation
“…Takao et al evaluated a series of 2‐azolylchromone derivatives ( 46a ‐ b , 47a ‐ b , and 48 ‐ 49 ) for MAO‐B inhibitory activity (Figure ). Compounds 46a ‐ b , 47a ‐ b , 48 , and 49 showed potent inhibitory activities against MAO‐B.…”
Section: Discovery and Development Of Mao‐b Inhibitors (2015‐2018)mentioning
confidence: 99%
“…2‐Azolylchromones ( 46a ‐ b , 47a ‐ b , and 48 ‐ 49 ) . hMAO, human monoamine oxidase; IC 50 , half maximal inhibitory concentration…”
Section: Discovery and Development Of Mao‐b Inhibitors (2015‐2018)mentioning
confidence: 99%